Realizing a High-Quality and Locally-Wise Global Tourism Business in Bali Based on Bali Provincial Regulation No. 5 of 2020 - Raditya Sudwika Utama, I Putu (CV. Publikasi Indonesia, 2025)
Bali, as one of the world’s top tourist destinations, faces a significant challenge in preserving its local cultural wisdom amidst the pressures of globalization. Bali Provincial Regulation No. 5 of 2020 on Standards for Bali Cultural Tourism serves as a concrete effort to address these challenges. This study aims to analyze the implementation of the regulation in balancing global demands with the preservation of local cultural values in Bali. The research methodology used is normative legal research with a document analysis approach, focusing on examining relevant legal texts and policies. This study also identifies various barriers to the effective application of the regulation. The main findings reveal that, although the regulation was designed to protect Bali's culture, its implementation is still hindered by factors such as inadequate monitoring, a lack of understanding among tourism business operators about local cultural values, and a mismatch between local norms and global standards. Additionally, the involvement of traditional villages in monitoring and policy formulation remains limited. This study recommends that the government strengthen monitoring mechanisms involving traditional communities, provide more space for traditional villages in decision-making, and introduce more progressive and concrete sanctions to ensure the effective application of Bali's cultural values. Thus, the implementation of this regulation can be more effective in protecting Bali’s cultural heritage amidst the growing challenges of globalization.